Zarządzanie uwagą we współczesnej gospodarce. Geneza i główne założenia koncepcji - Aluchna, Maria; Pindelski, Mikołaj; Mrówka, Rafał; Obłój, Tomasz (The concept of attention economy. Orgin and main assumptions, 2006)
The paper focuses on the analysis of new management concept known as attention economy. The aim of the paper is to present the world literature review, concentrating mostly on the origin of the attention economy, the determinants that influence the development of the concept as well as its main features. Additionally, the results of the approach proposed by attention economy for organizations, societies and economies are discussed. The concept of attention economy offers new and relatively revolutionary perception of economic environment. Attention economy indicates dramatic changes in structure, characteristics and functioning rules of current economic systems pointing at the importance of information, information exchanges and analysis. The importance of resources, capital and skills is replaced by the importance of information collected and attracting attention of customers and employees. Thus the emphasis of management is shifted from traditional forms of activities cooperation towards new perception of organizing, strategy formulation and marketing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 423-431